Entre o Império e a NATO Portugal e os Estados Unidos da América (1949-1961) - Marcos, Daniel (Contemporânea, 2022)
This book addresses the evolution of Portuguese-American relations between 1946 and 1961, taking into account the two aspects that conditioned the relationship between the two countries: the North American interest in having the Lajes base in the Azores and the Portuguese government's commitment to secure Washington's support for maintaining its colonial policy. Contrary to what historiography indicated as a "golden period" in the understanding between Lisbon and Washington, the book demonstrates that the Cold War climate and the internationalization of the Portuguese colonial issue conditioned relations between the two countries. Without ever reaching a breaking point, the relationship between the two countries was always constrained by the evident differences in approach regarding the position of the West in relation to the Afro-Asian world, with Portugal linking the American presence in the Azores with the North American need to, if not support, turn a blind eye to the maintenance of Portuguese colonial policy.